2018
DOI: 10.1002/pssr.201800131
|View full text |Cite
|
Sign up to set email alerts
|

Tb/Ni/TiN Stack for Ultralow Contact Resistive Ni‐Tb‐InGaAs Alloy to n‐In0.53Ga0.47As Layer

Abstract: This paper presents a Tb/Ni/TiN stack that can act as a metallic contact for n-In 0.53 Ga 0.47 As layer with lower specific contact resistivity. Tb/Ni/TiN layers are deposited sequentially on n-In 0.53 Ga 0.47 As via sputtering and Ni(Tb)-InGaAs alloy is formed using rapid thermal annealing. The ultralow specific contact resistivity (ρ c ) of 7.98 Â 10 À9 Ω cm 2 is obtained between Ni(Tb)-InGaAs and n-In 0.53 Ga 0.47 As layers, which is more than two orders of magnitude lower than that of a control sample with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ohmic contact formation between the p-InP substrate and the AuBe/Au metal electrode is an essential factor to improve η up 14.37% by receding the series resistance. Recently, Li et al [157] proposed Tb/Ni/TiN metal stack for n-InGaAs with lower specific ρ c of 7.98 × 10 −9 Ω cm 2 . Increasing the dopant concentration in the Ni-InGaAs alloy and the lowering the barrier height between Ni-InGaAs and n-In 0.53 Ga 0.47 As successfully increase the contact resistance.…”
Section: Metal Contact Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ohmic contact formation between the p-InP substrate and the AuBe/Au metal electrode is an essential factor to improve η up 14.37% by receding the series resistance. Recently, Li et al [157] proposed Tb/Ni/TiN metal stack for n-InGaAs with lower specific ρ c of 7.98 × 10 −9 Ω cm 2 . Increasing the dopant concentration in the Ni-InGaAs alloy and the lowering the barrier height between Ni-InGaAs and n-In 0.53 Ga 0.47 As successfully increase the contact resistance.…”
Section: Metal Contact Optimizationmentioning
confidence: 99%
“…Recently, studies used an InGaAs cell in multi-junction such as GaInP/GaAs/InGaAs [103], and tandem cells such as GaAs/InGaAs [154], which aim to increase the total efficiency and to extend the power harvesting into the mid-infrared wavelengths. Several studies reported the crystal defects of lattice mismatch InGaAs cells for bandgap from 0.55 to 0.6 eV [155], characterization of the cell performances and optimization of the structure design [156][157][158][159].…”
Section: Introductionmentioning
confidence: 99%